2013
DOI: 10.1002/14651858.cd009632.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Mammography in combination with breast ultrasonography versus mammography for breast cancer screening in women at average risk

Abstract: Mammography in combination with breast ultrasonography versus mammography for breast cancer screening in women at average risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 59 publications
0
36
0
2
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Among these, 7 reviews assessed a screening method only for the general population, 7 only for a specific subpopulation and 3 for both. The reviews assessed screening approaches for the following types of cancer: cancer in general (n = 2), bladder (n = 1), breast (n = 4), colorectal (n = 2), hepatic (n = 1), lung (n = 1), nasopharyngeal (n = 1), esophageal (n = 1), oral (n = 1), prostate (n = 1), testicular (n = 1) and uterine (n = 1).…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Among these, 7 reviews assessed a screening method only for the general population, 7 only for a specific subpopulation and 3 for both. The reviews assessed screening approaches for the following types of cancer: cancer in general (n = 2), bladder (n = 1), breast (n = 4), colorectal (n = 2), hepatic (n = 1), lung (n = 1), nasopharyngeal (n = 1), esophageal (n = 1), oral (n = 1), prostate (n = 1), testicular (n = 1) and uterine (n = 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…• Screening using urinary dipsticks for reducing morbidity and mortality; 11 • Mammography versus mammography plus ultrasonography for breast cancer screening testing in women at average risk; 13 • Screening for nasopharyngeal cancer; 20 • Screening for esophageal cancer; 21 • Screening for testicular cancer; 24 • Follow-up strategies after treatment (large loop excision of the transformation zone (LLETZ)) for cervical intraepithelial neoplasia (CIN): Impact of human papillomavirus (HPV) test. 25 Thus, no recommendations in relation to the topics of these six systematic reviews can be made until primary studies, preferably…”
Section: Screening For Prostate Cancermentioning
confidence: 99%
“…A mamografia não é uma técnica perfeita, e em algumas mulheres com mamas densas, os tumores são difíceis de distinguir. A adição da ultrassonografia nestas mulheres irá detectar os tumores que não foram detectados pela mamografia [13][14].…”
Section: Discussionunclassified
“…It has a high false positive rate and is less sensitive than breast MRI (Kolb et al, 1998;Buchberger et al, 1999;Gordon, 2002) which might increase the number of biopsies and unnecessary treatment. Based on systematic review, little evidencebased support is found to confirm the well-recognized value of ultrasonography as an adjunct to mammography in the detection of breast cancer in clinical practice and routine use of ultrasonography as an adjunct screening tool in women at average risk for breast cancer is not justified (Flobbe et al, 2002;Gartlehner et al, 2013). In Thailand, the limitations to implement widespread screening ultrasound include a shortage of qualified personnel to perform and interpret the examination and lack of standardized scanning protocols.…”
Section: Comparison Of Mammography In Combination With Breast Ultrasomentioning
confidence: 99%